One Typology for a Big Word: Office of Diversity - Lopez-Pineiro, Sergio (UI Scholars Hub, 2021)
Architecture’s original project was the invention of interiority, an enclosed area delimited from its context and made available for a narrowly defined public, function, and meaning. This original project was expanded during the Enlightenment with the concept of type as a method for producing architecture and establishing social institutions for molding subjectivities. This quest for interiority has reached its completion with world capitalism and its associated complexes, which, as Michael Hardt and Antonio Negri have argued, are an interior without any possible or imaginable outside. In response to this condition, this essay argues that the original project of architecture—the conception and design of interiority—needs to be replaced by a new one: the conception and design of openings. To demonstrate this, I have assembled Typologies for Big Words, a series of projects that redefines the concept of type through a selection of building and landscape types proposed as openings within this global interior. Using Byung Chul-Han’s portrayal of contemporary society as an achievement society occupied by achievement-subjects, I present one of these projects as an example, Office of Diversity, as an opening for the production of non-paradigmatic subjectivities.